The expressive function of the mezzanine in television drama (Journal of the College of Basic Education, 2023)
Television drama witnessed a development in the embodiment and in the methods of presenting and expressing the contents and values that the creator of the work seeks to deliver to the recipient through the drama. And the content of a certain emotion and its delivery to the viewer, in addition to including aesthetic values in the artwork.Everything that goes into the directorial process falls within the responsibility of the mezzanine, especially the movement, which is represented by moving the actor and the assets in addition to the movement of the camera and the arrangement of these movements to express ideas and contents and give the work expressive and aesthetic values in the case of optimal and studied use by the director in the TV drama, and accordingly we can put a problem Search in the form of an agency question:What are the ways of employing the mise-en-cine expressively in the TV drama?